Missense mutation in sterile α motif of novel protein SamCystin is associated with polycystic kidney disease in (cy/+) rat - Brown, Joanna H.; Bihoreau, Marie-Thérèse; Hoffmann, Sigrid; Kränzlin, Bettina; Tychinskaya, Yulia; Obermüller, Nicholas; Podlich, Dirk; Böhn, Susanne; Kaisaki, Pamela J.; Megel, Natalia; Danoy, Patrick; Copley, Richard R.; et al. (Journal of the American Society of Nephrology, 2005)
Autosomal dominant polycystic kidney disease (PKD) is the most common genetic disease that leads to kidney failure in humans. In addition to the known causative genes PKD1 and PKD2, there are mutations that result in cystic changes in the kidney, such as nephronophthisis, autosomal recessive polycystic kidney disease, or medullary cystic kidney disease. Recent efforts to improve the understanding of renal cystogenesis have been greatly enhanced by studies in rodent models of PKD. Genetic studies in the (cy/+) rat showed that PKD spontaneously develops as a consequence of a mutation in a gene different from the rat orthologs of PKD1 and PKD2 or other genes that are known to be involved in human cystic kidney diseases. This article reports the positional cloning and mutation analysis of the rat PKD gene, which revealed a C to T transition that replaces an arginine by a tryptophan at amino acid 823 in the protein sequence. It was determined that Pkdr1 is specifically expressed in renal proximal tubules and encodes a novel protein, SamCystin, that contains ankyrin repeats and a sterile α motif. The characterization of this protein, which does not share structural homologies with known polycystins, may give new insights into the pathophysiology of renal cyst development in patients.